Seroprevalence of leptospirosis in public cleaning workers of the district of San Juan Bautista, Ayacucho - Quispe-Girón, Claudia (2017)
The aim of this study was to determine the prevalence and associated factors of human leptospirosis in public cleaning workers of the district of San Juan Bautista, Ayacucho, Peru. An epidemiological survey was conducted and blood samples were analyzed by ELISA IgM and agglutination (MAT) for the determination of Leptospira serovars. Of the 41 workers tested, 25 (62.5%) were male and 16 (37.5%) were women. Three workers resulted positive (7.32%), two men and one woman. None of the possible risk factors was statistically significant. The titres of the three positive cases were 1/3200, 1/1600 and 1/3200 against serovar Varillal.